EMERGENCY OF YELLOW PASSION FRUIT UNDER SALT STRESS ON DIFFERENT SUBSTRATES - Ribeiro, A. A.; Moreira, F. J. C.; Seabra Filho, M.; Menezes, A. S. (Revista Brasileira de Engenharia de Biossistemas, 2016)
Salinity is become one of the main problems affecting crop productivity in arid and semi-arid regions. Therefore, the aim of the present study was to evaluate the effects of irrigation water salinity and two substrates in the emergence of yellow passion fruit. The experiment was conducted in laboratory and field conditions in the Sobral-CE region. The experimental design was adopted in randomized blocks in factorial analysis scheme 5 x 2, referring to the effects of irrigation water salinity (0.27, 1.5, 2.5, 3.5, 4.5 dS m-1) in two substrates: manure + sand (S1) and only cattle manure (S2) with four replications, totaling 40 experimental plots. The variables analyzed were: first count, emergence percentage, emergence speed index and average time of emergency. With the results, it was found that the emergence of yellow passion fruit seeds was not influenced by the evaluated substrates. The seeds of yellow passion fruit tolerated salts only up to 1.5 dS m-1.